Health promotion in the workplace - Magnavita, Nicola; De Lorenzo, Giuseppe; Sacco, Angelo (La Medicina del Lavoro, 2014)
We read with great interest the case-report of Riva et al. [4]  that pointed out the importance of  unimpaired hearing in the occupational skills of future physicians. Attention should be given to the fact that hearing impairment in most health care activities may compromise the safety of workers and  third parties. We have described the case of a nurse with hearing impairment who cannot work safely with colleagues wearing a respiratory mask in airborne isolation rooms without lip reading [2]. We therefore fully agree with the statement that hearing disorders should be accurately investigated by occupational physicians during fit to work assessment of medical students and other health care workers. Hearing is important  for health care workers in order to communicate effectively with patients, staff, and colleagues.The case report also leads us to another consideration. In fact, it indicates a clear direction for health surveillance, which is not only the prevention of damage caused by occupational exposure, but also the active search for and prevention of all morbid states that can interfere with work ability. 20 years ago a health promotion program for medical students, funded by the Institute for university studies “Opera Universitaria” of the Università Cattolica, enabled us to demonstrate that more than 8% of the students, enrolled in the first year of the degree course in medicine, had an early deficit in auditory function, correlated with use of headphones or listening to loud amplified music [3].This information on noise hazard and its possible consequences for medical practice prevented those students from developing  severe hearing impairment.The working environment is often seen as the ideal place for activities of health promotion. Regular  surveillance of workers enables us to observe changes induced by health care intervention over time at a relatively reduced cost. The key for successful health promotion programs lies in worker participation. Many occupational hazards, such as night and shift work, driving, fatigue and other critical tasks cannot be effectively controlled if workers do not improve their sleeping habits, diet, and alcohol use. However, workers do not always understand the importance of the proposed actions and for this reason many of them do not follow the physician's advice [1]. An important factor for the success of health promotion campaigns is the close connection  between the proposed objectives and work performance. If workers understand this link, their compliance with proposed lifestyle changes will improve and the campaign will be a success.